Catalogue of the type material in the entomological collection of the University of La Laguna (Canary Islands, Spain). I. Arachnida - Reboleira, Ana Sofia P. S.; Pérez, Antonio José; López, Heriberto; Macías–Hernández, Nuria; de La Cruz, Salvador; Oromí, Pedro (Zootaxa, 2012)
A catalogue of arachnid type specimens of the collection kept at the Department of Animal Biology, University of LaLaguna (Spain) is presented. It harbours type material of 104 species belonging to 23 families of arachnids, representedby 21 holotypes and 164 paratypes for 23 species of pseudoscorpions, and 49 holotypes, 218 paratypes and 3 syntypes for81 species of spiders. This collection is using the criteria and standards of the Global Biodiversity Information Facility(GBIF) for cataloguing and computerization of the specimens. Type specimens were checked with the original descriptions, and relevant additional information from original labels not included in GBIF was registered.